Public Libraries as Partners in Confronting the Overdose Crisis: A Qualitative Analysis. Issue 3 (July 2021) - Lowenstein, Margaret; Feuerstein-Simon, Rachel; Sheni, Risha; Dupuis, Roxanne; Kinsey, Eliza Whiteman; Luna Marti, Xochitl; Cannuscio, Carolyn
Background: The overdose crisis is affecting public libraries. In a 2017 survey of public librarians, half reported providing patrons support regarding substance use and mental health in the previous month, and 12% reported on-site drug overdose at their library in the previous year. Given the magnitude of the overdose crisis and the fact that public libraries host 1.4 billion visits annually, our aim was to understand how libraries currently assist with substance use and overdose and how they can further address these issues. Methods: We conducted semi-structured interviews with 44 public library staff from across the U.S. attending a national meeting in March 2018. Interviews addressed attitudes and experiences regarding drug use, overdose, and overdose response in libraries. We analyzed interviews using thematic content analysis guided by the Consolidated Framework for Implementation Research. Results: Participants were from 26 states. Among libraries in this sample, 14% had experienced an on-site drug overdose and 7% stocked naloxone at the time of study. Nearly all participants reported substance use as a prominent concern among patrons and their families, as well as in the library itself. Many participants were willing to provide support to patrons and even administer naloxone, but they often lacked preparation, resources, or institutional support. Participants also expressed interest in providing information or referrals to people who use drugs (PWUD), but such efforts were often stymied by inadequate community resources. Finally, participants expressed interest in strengthening partnerships between public libraries and health and social service organizations. Conclusions and Relevance: Public library staff routinely engage PWUD, and based on prior studies, nearly 2, 000 of U.S. public libraries can expect an on-site overdose in the next year. Findings from our work highlight the need for further study about how public libraries can act as part of comprehensive, community-based strategies to address the opioid epidemic.